Differentially expressed genes in transcriptomes of monoecious and pistillate lines of castor (Ricinus communis L.): Differentially expressed genes in transcriptomes of monoecious and pistillate lines of castor (Ricinus communis L.) - M SUJATHA; M TARAKESWARI; C LAVANYA; RUKAM SINGH TOMAR; MIR ASIF IQUEBAL (Journal of Oilseeds Research, 2020)
Transcriptome sequencing of 12 tissues from different sex morphs was carried out to identify differentially expressed genes governing sex expression in castor. Comparative analysis of different transcriptomes resulted in identification of transcription factors (1054), DE unigenes (540), miRNA targets, which will pave way for understanding the role of key genes involved in sex mechanism in castor.